Case report: A diabetic patient with cryptococcal meningoencephalitis complicated by post-infectious inflammatory response syndrome - Chen, Qinghua; Yu, Weitong; Wang, Xuyi; Zhao, Chenxi; Wang, Pin; Sun, Lin; Xu, Linlin; Xu, Yingying (Frontiers in Immunology, 2024)
We report on a previously non-HIV-diagnosed, 47-year-old male diagnosed with diabetes mellitus (DM) and cryptococcal meningoencephalitis, who was referred to our institution for antifungal treatment. During the course of treatment, due to the development of refractory intracranial hypertension, Ommaya reservoirs were employed for cranial pressure reduction. The patient gradually recovered during subsequent antifungal therapy; however, symptoms worsened in the third month of treatment, leading to consideration of post-infectious inflammatory response syndrome (PIIRS) on examination. Once diagnosed, the symptoms improved significantly after approximately 130 days of treatment with additional corticosteroids.